The awareness and level of implementation of e-commerce among SMEs in Malaysia - Mahmood, Ahmad; Jahari, Nor Azah (2005)
Electronic data interchange (EDI), direct link-ups with suppliers, internet, extranet, electronic catalogue ordering and e-mail are variety of forms of e-commerce.In today environment, e-commerce or electronic commerce has become one of the important forces to shaping business.Recent research has shown that, despite technology facilitating improve business practice in term of developing electronic markets, electronic data interchange and internet commerce (Whiteley, 2000), a number of SMEs have not taken advantage of this new mode of carrying out business (Smyth and Ibbotson, 2001).This research is to investigate and to know the degree of adoption, awareness and level of implementation of e-commerce in Malaysia Small and Medium Enterprise (SMEs).Finally, some suggestions have been made, which might be followed by such firms in seeking to enhance their performance in e-commerce.